Case study methodology for teaching foreigners - Solovyova, Olga; Соловйова, Ольга Володимирівна (Дніпровський національний університет імені Олеся Гончара, 2022)
The case study method is a method of active analysis of a problem situation, based on learning by solving specific situational problems. The essence of the case study method: foreign students, divided into groups, must analyze the situation and work out a practical solution; the end of the process - the evaluation of the proposed algorithms and their discussion within the framework of a general discussion in the context of the problem posed.